The Ideal Educator According to Abd Al-Salām Yāsīn in Forming The Character of Contemporary Students - Wan Muhammad Fariq; Gamal Abdul Nasir Zakaria (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
Educators are an essential element in the world of education. To become a successful educator, appropriate strategies are needed to convey learning appropriately. A significant figure from Morocco named Abd al-Salām Yāsīn (1928-2012) compiled notes in his book "Muzakkarāt fi Al-Tarbiyyah li Madāris al-Mu'allimīn wa Al-Mu'allimāt about education in 1963. This paper tries to look at the from the book about the ideal educator according to Abd al-Salām Yāsīn. The type of research used is qualitative research (non-interactive) with content analysis techniques. The researcher found that there are 8 (eight) ideal educator concepts according to Abd al-Salām Yāsīn. Among them: (1) creative; (2) perfect physique; (3) simple and attractive appearance; (4) have intelligence; (5) have the character of compassion, emotional intelligence and empathy; (6) is fair; (7) sensitive; and (8) authoritative. All of his ideas are still relevant to the world of education today.